Any place I hang my hat - Isaacs, Susan, 1943- (New York : Scribner, 2004)
Growing up under the care of her financially disadvantaged grandmother, Amy Lincoln launches a journalism career when an encounter with a student who claims he's the illegitimate son of a presidential candidate sets Amy wondering about her own mother
Keywords: Women journalists -- Fiction; Presidential candidates -- Fiction; Political campaigns -- Fiction; Mothers and daughters -- Fiction; Political fiction; Domestic fiction; Love stories